Regions of the Moloney murine leukemia virus genome specifically related to induction of promonocytic tumors. - Wolff, L (1990)
Moloney murine leukemia virus (MuLV) can be a potent inducer of promonocytic leukemias in mice that are undergoing a chronic inflammatory response. The neoplasms are, at least in part, associated with insertional mutagenesis of the c-myb locus. Evidence is presented for the existence of at least two genetic elements of the virus that are crucial to induction of this disease but are not required for viral replication in hematopoietic tissues or induction of lymphoid disease. These genetic elements were detected by testing the pathogenicity of recombinants between Moloney and Friend MuLVs, the latter of which is nonleukemic to myeloid cells under these conditions, and by testing Moloney MuLV-based viruses that have nonretroviral sequences inserted at specific endonuclease sites in their long terminal repeats (LTRs). Analysis of the Moloney/Friend recombinants showed that there are sequences within the structural gene domain of Moloney, but not Friend, MuLV that are necessary for promonocytic leukemia, whereas the LTRs of the MuLVs are equally effective for promonocytic tumor formation and insertional mutagenesis of the c-myb gene. Experiments with viruses which were mutagenized in the LTR by insertions demonstrated that there is a specific genetic element in the U3 region of the LTR of Moloney MuLV, upstream of the 75-base-pair enhancer which, when interrupted, results in loss of leukemogenicity for cells in the monocytic lineage but not cells in the lymphoid lineage. We conclude, therefore, that promonocytic leukemia induction, in Moloney MuLV-infected mice undergoing a chronic inflammatory response, requires specific sequences in the structural gene region of Moloney MuLV as well as other sequences in the regulatory region of the virus.